The Effect of Job Training, Reward, and Punishment on Employee Work Performance at the Indonesian Harmoni Healthy Traditional Health Center - Amal Prihatono; Muljadi; Puspo Wardoyo; Leny Candra Kurniawan (Budapest International Research and Critics University, 2022)
Employee work performance is still a specific problem for each agency. The preliminary study on 1 staff manager that the number of customer visits has decreased in the last 3 years, in 2019 (552 people), 2020 (513 people), and 2021 (486 people), the satisfaction of 5 customers was 68% satisfied, 32% dissatisfied. The aim is to analyze the effect of job training, reward, and punishment on work performance. Methods one group pre-post test. The population was all employees at the Indonesian Harmoni Healthy Traditional Health Center, Malang including 10 therapists, 4 administrative officers, 2 cleaning services, total sampling, questionnaire, interview sheets, Wilcoxon using SPSS V.16. The results that the age of respondents was 20-35 years (56.2%), therapists 62.5%, male sex (62.5%), the employee's work experience <5 years (56.2%), work performance before training was bad (75%) after that was good (81.2%); work performance before giving rewards, punishments were bad (75%) after that was good (81.2%). The results showed work performance before or after job training (p=0.003), before, and after giving rewards, punishment (p=0.003). The conclusion showed the provision of training effects, rewards, punishments are significant. Therefore, the importance of human resources management which good as an effort to improve work performance.